2020
DOI: 10.1038/s41419-020-2268-8
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA HOTAIR knockdown enhances radiosensitivity through regulating microRNA-93/ATG12 axis in colorectal cancer

Abstract: Colorectal cancer (CRC) is a global healthcare problem. Radioresistance is a huge setback for CRC radiotherapy. In this text, the roles and molecular mechanisms of long non-coding RNA HOTAIR in CRC tumorigenesis and radioresistance were further investigated. ATG12 mRNA, HOTAIR, and microRNA-93 (miR-93) levels were measured by quantitative reverse transcription polymerase chain reaction (RT-qPCR) assay. Protein levels of LC3 I, LC3 II, p62, ATG12, cleaved caspase 3, Bax, and Bcl-2 were detected by western blott… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(61 citation statements)
references
References 37 publications
4
57
0
Order By: Relevance
“…Additionally, lncRNAs control autophagy mainly by directly or indirectly regulating ATG expression (146). As an example, knockdown in colorectal cancer cells of homeobox transcript antisense intergenic RNA (HOTAIR), a lncRNA that has been widely studied, induces upregulation of miR-93 and a downregulation of ATG12, resulting in a blockage of autophagy and the induction of apoptotic cell death (147). In hepatocellular carcinoma, the lncRNAs phosphatase and tensin homolog pseudogene 1 (PTENP1) activate autophagy, interacting with miR-17, miR-19b, and miR-20a, denying their targeting of the autophagy genes ULK1, ATG7 and p62/SQSTM1, and the tumor suppressor PTEN.…”
Section: Autophagy and Non-coding Rnasmentioning
confidence: 99%
“…Additionally, lncRNAs control autophagy mainly by directly or indirectly regulating ATG expression (146). As an example, knockdown in colorectal cancer cells of homeobox transcript antisense intergenic RNA (HOTAIR), a lncRNA that has been widely studied, induces upregulation of miR-93 and a downregulation of ATG12, resulting in a blockage of autophagy and the induction of apoptotic cell death (147). In hepatocellular carcinoma, the lncRNAs phosphatase and tensin homolog pseudogene 1 (PTENP1) activate autophagy, interacting with miR-17, miR-19b, and miR-20a, denying their targeting of the autophagy genes ULK1, ATG7 and p62/SQSTM1, and the tumor suppressor PTEN.…”
Section: Autophagy and Non-coding Rnasmentioning
confidence: 99%
“…In colorectal cancer, HOTAIR upregulated ATG12 expression by sponging miR-93. Knockdown of HOTAIR and ATG12, or overexpression of miR-93, suppressed autophagy and restored radiosensitivity in colorectal cancer cells [ 58 ]. In chondrosarcoma, elevated expression of HOTAIR predicted advanced tumor stage and poor survival.…”
Section: Cernas-regulated Autophagy In Cancermentioning
confidence: 99%
“…The oncogenic roles of LINC00160 and HCG11 have been confirmed not only in vitro but also in murine xenograft models. Likewise, SLCO4A-AS1 [ 55 ] and HOTAIR [ 58 ] were found to be overexpressed in colorectal cancers, and acted as oncogenes in in vitro and in vivo studies. PVT1 overexpression indicated poor clinical outcomes in patients with pancreatic cancers [ 32 ].…”
Section: Cernas As Potential Therapeutic Targets In Cancersmentioning
confidence: 99%
“…Abundant research has demonstrated that pathological changes in lncRNAs exert critical regulation in all aspects of the initiation and development of CRC. [7][8][9] For example, Ding et al discovered that the lncRNA CASC9 was abnormally upregulation within CRC tissues and promoted the viability, migration, and invasion of CRC cells, 8 and Yang et al showed that the lncRNA XIST, a novel diagnostic biomarker in CRC, was associated with poor prognosis through the downregulation of METTL14. 9 These data demonstrate that lncRNAs play important roles in tumorigenesis and tumor development.…”
Section: Introductionmentioning
confidence: 99%